The Effect of Calcium Sodium Phosphosilicate on Dentin Hypersensitivity: A Systematic Review and Meta-Analysis. - Mengjiao Zhu; Jialing Li; Bin Chen; Li Mei; Liang Yao; Jinhui Tian; Huang Li (PLoS ONE)
Objective To investigate the effect of calcium sodium phosphosilicate (CSPS) in treating dentin hypersensitivity (DH) and to compare this effect to that of a negative (placebo) control. Materials and methods Several databases, including Medline, EMBASE, Web of Science, The Cochrane Library, and the Chinese Biomedical Literature Database, were searched to identify relevant articles published through January 2015; grey literature (i.e., academic literature that is not formally published) was also searched. Two authors performed data extraction independently and jointly using data collection forms. The primary outcome was the DH pain response to routine activities or to thermal, tactile, evaporative, or electrical stimuli, and the secondary outcome was the side effects of CSPS use. Each study was evaluated using the Cochrane Collaboration tool for assessing risk bias. Meta-analysis of studies with the same participant demographics, interventions, controls, assessment methods and follow-up periods was performed. The Grading of Recommendations Assessment Development and Evaluation System was used to assess the quality of the evidence and the risk of bias across studies. Results Meta-analysis demonstrated that toothpaste containing 5% CSPS was more effective than the negative control at relieving dentin sensitivity, with the level of evidence classified as "moderate". In addition, prophylaxis paste containing 15% calcium sodium phosphosilicate was favored over the negative control at reducing post-periodontal therapy hypersensitivity, with the level of evidence categorized as "low". Only two studies reported side effects of CSPS use. Conclusions The majority of studies found that calcium sodium phosphosilicate was more effective than the negative control at alleviating DH. Because strong evidence is scarce, high-quality, well-designed clinical trials are required in the future before definitive recommendations can be made.